Why Are the Wages of Job Changers So Procyclical? - Barlevy, Gadi (Journal of Labor Economics, 2001)
Evidence on wage cyclicality shows job changers have more procyclical wages than job stayers. Previous work argued this arises because workers gain greater access to jobs in sectors such as manufacturing that offer high wages. This article argues that workers who switch jobs in booms enter temporary jobs with unemployment risk and are merely compensated for subsequent losses. I demonstrate that the two explanations can be distinguished using the relationship between unemployment insurance and wage cyclicality among job changers. The evidence supports the compensation hypothesis; that is, that job changers might not experience real gains from higher‐paying jobs in booms.